The Effect of Implementing the Two Stay Two Stray Model on the Mathematics Learning Outcomes of Fourth-Grade Students at SD Negeri 1 Pulau Beringin, South OKU - Sartika, Sri Dewi; Muhamad Afandi; Ines Tasya Jadidah (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study discusses the impact of the implementation of the Two Stay Two Stray model on students' learning outcomes in Mathematics in grade IV at SDN 1 Pulau Beringin, Oku Selatan. The purpose of this research is to determine the effect of the application of the Two Stay Two Stray model on students' learning outcomes in Mathematics in grade IV at SDN 1 Pulau Beringin, Oku Selatan. This study uses an experimental research design with a quantitative approach, involving treatment. The design used is the One-Group Pretest-Posttest Design. The population of this study consists of all children at SDN 1 Pulau Beringin, while the sample is grade IV students, totaling 28 students, with proportional sampling technique. Learning outcomes were measured using a student test instrument, while validity was determined using Pearson's Product Moment correlation and reliability using Cronbach's Alpha. Data analysis prerequisites included the Kolmogorov-Smirnov normality test, while hypothesis testing used the Paired Sample T-Test. The results indicate that the application of the Two Stay Two Stray model has an impact on students' learning outcomes in Mathematics in grade IV at SDN 1 Pulau Beringin. The effect of this media is seen from the hypothesis test results. At a 5% significance level, it is proven that there is an influence of the Two Stay Two Stray model on students' learning outcomes, as indicated by the calculated t-value > t-table. Therefore, the null hypothesis is rejected, meaning the alternative hypothesis is accepted, and it can be concluded that the Two Stay Two Stray model affects students' learning outcomes.